Preparation method of high-temperature anti-ablation (Hf-Zr-Nb) C ternary carbide medium-entropy ceramic

The (Hf-Zr-Nb)C ternary carbide medium-entropy ceramic prepared by carbothermal reduction method and pressureless sintering method solves the problem of insufficient anti-oxidation/ablation performance of single-component ceramics in high-temperature ablation environment. Improved ablation resistance and cost-effectiveness achieved.

CN119330716AActive Publication Date: 2025-01-21HENAN ACAD OF SCI CARBON MATRIX COMPOSITES RES INST
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411515069.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing single-component ultra-high temperature ceramics have insufficient ablation resistance in an environment where ultra-high-speed, ultra-high-temperature oxygen-containing gas flow is washed, and cannot effectively protect the inside of the ceramic.

Method used

(Hf-Zr-Nb)C ternary carbide medium-entropy ceramics are prepared using carbothermal reduction method and pressureless sintering method. By simplifying the sintering process and reducing preparation costs, a ceramic material with excellent high-temperature stability and ablation resistance is formed. .

Benefits of technology

This ceramic material can maintain structural integrity under the ablation condition of an oxyacetylene flame at 2200°C for 60 seconds, significantly improving its ablation resistance and is suitable for hot-end components of hypersonic aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330716A_ABST
    Figure CN119330716A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, and discloses a preparation method of high-temperature anti-ablation (Hf-Zr-Nb) C ternary carbide medium-entropy ceramic. The preparation method comprises the following steps: firstly, mixing HfO2, ZrO2, Nb2O5 and C powder, then carrying out heat treatment in a high-temperature heat treatment furnace, and preparing (Hf-Zr-Nb) C medium-entropy ceramic powder by utilizing a carbon thermal reduction reaction; performing compression molding on the powder to obtain a ceramic block; and finally, sintering the ceramic block by using pressureless sintering equipment to obtain the (Hf-Zr-Nb) C ternary carbide medium-entropy ceramic. Compared with an existing precursor impregnation cracking and spark plasma sintering densification technology which generally has the problems of expensive equipment, high energy consumption and low yield, the pressureless sintering technology which is simple and convenient in process is adopted, so that the production cost is greatly reduced, and the yield is improved. The medium-entropy carbide ceramic block has relatively good ablation resistance. Technical support is provided for application of the high-temperature anti-ablation medium-entropy carbide ceramic material in hot-end components of aerospace vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a method for preparing high-temperature ablation-resistant (Hf-Zr-Nb)C ternary carbide medium-entropy ceramics. Background Art

[0002] At present, countries around the world are increasingly in need of long-lasting hypersonic aircraft, which means they must serve in harsh environments. Some key structural components such as nose cones, leading edges, air rudders, engine combustion chambers and nozzles will be subjected to ultra-high temperatures, high pressures and long-term ablation tests of "high enthalpy chemical non-equilibrium flow". In view of the above harsh service environment, it is necessary for us to develop new material systems and explore new thermal protection theories. The performance of thermal protection materials not only determines the speed limit of hypersonic aircraft, but also directly affects its service life. It is the basic guarantee for the iterative development of aerospace equipment.

[0003] Ultra-high temperature ceramics have become the most commonly used thermal protection materials in aerospace due to their high melting point, high strength and good resistance to thermal shock. Among them, single-component thermal protection ceramic materials (ZrB2, HfB2, ZrC, HfC, TaC, HfN, etc.) have a fast oxidation / ablation rate in the environment of high-speed, high-temperature and strong airflow erosion, and can no longer meet the current service performance requirements for the hot end components of hypersonic aircraft. Therefore, the research and development of new ultra-high temperature materials with better performance and solving the problem of high-stability thermal protection have become the top priorities in the development of hypersonic aircraft. Multi-component ultra-high temperature carbide ceramics have higher hardness and elastic modulus, lower thermal conductivity and better oxidation / ablation resistance. They are expected to solve the problems of insufficient stability and poor oxidation / ablation resistance of traditional ultra-high temperature carbide ceramics in extreme environment service, and become an important candidate for thermal protection materials for the hot end components of hypersonic aircraft.

[0004] Reference 1 "Huang B, Chen L, Bai S. Bulk ultrafine binderless WC prepared by spark plasma sintering [J]. Scripta Materialia, 2006, 54 (3): 441-445." Using spark plasma sintering process, without adding any binder phase, ultrafine WC powder with a diameter of about 200nm was prepared. Under the binderless sintering process at 1773K and 240s, WC was fully densified and showed excellent mechanical properties. However, pressure-assisted sintering equipment such as spark plasma sintering is very expensive and consumes a lot of energy. It is not suitable for mass production and is only suitable for the processing of small-sized and simple-shaped components.

[0005] Reference 2 "Ren J, Zhang Y, Zhang J, et al. Effects of HfC nanowire amount on the microstructure and ablation resistance of CVD-HfC coating [J]. Ceramics International, 2018, 44 (10): 11340-9." HfC ceramic coating was prepared on the surface of C / C composite material by chemical vapor deposition. 2 The failure occurred after continuous ablation for 120s. This is because the HfO2 formed by oxidation of HfC is loose and porous after long-term ablation. During the ablation process, oxygen passes through these loose structures and diffuses to the internal SiC layer and even the C / C matrix, aggravating the damage of the C / C composite material. In addition, since the loose skeleton structure of HfO2 cannot resist the mechanical erosion during the ablation process, the oxide layer cracks and falls off severely, so the ablation resistance of HfC ceramics is poor.

[0006] Reference 3 "Li B, Li H, Yao X, et al. Preparation and ablation resistance of ZrC nanowires-reinforced CVD-ZrC coating on sharp leading edge C / C composites [J]. Applied Surface Science, 2022, 584." ZrC ceramic coating was prepared on the surface of C / C composite by chemical vapor deposition. 2 The ZrO2 formed by the oxidation and ablation of ZrC has similar properties to HfO2. After a long period of ablation, the ZrO2 oxide layer is still loose and porous, which cannot effectively inhibit the diffusion of oxygen. In addition, the loose skeleton structure of ZrO2 cannot resist the mechanical erosion during the ablation process, resulting in severe cracking and shedding of the ZrO2 oxide layer. Therefore, the ablation resistance of ZrC ceramics is also poor.

[0007] In summary, the preparation cost of ceramic blocks by pressure-assisted sintering is high, the energy consumption is large, and it is not conducive to large-scale production. Although HfC and ZrC ceramics have many advantages, such as high melting point (3890℃ and 3540℃), high thermal stability, and low vapor pressure, the anti-ablation effect of single-component ceramics is still very limited. In a high-temperature oxygen environment, a single HfC ceramic will form an HfO2 oxide layer on the surface. Since HfO2 undergoes a phase change at high temperature, the huge phase change stress will cause serious damage to the oxide layer. After ablation, a single ZrC material will form loose and porous ZrO2, which is difficult to withstand the scouring effect of high-speed heat flow. Therefore, in the face of a more severe ablation environment, a single HfC ceramic or ZrC ceramic cannot effectively protect the interior of the ceramic. In summary, it is crucial to use a low-cost and simple process method to prepare a new type of high-performance ultra-high temperature ceramic. Summary of the invention

[0008] In order to solve the problem of insufficient ablation resistance of single-component ultra-high temperature ceramics in an atmosphere flushed by extremely high-speed, ultra-high temperature oxygen-containing gas flow, the present invention proposes a high-temperature ablation-resistant (Hf-Zr-Nb)C ternary carbide medium-entropy ceramic by simplifying the sintering process and reducing the preparation cost. Using HfO2 powder, ZrO2 powder, Nb2O5 powder and C powder as raw materials, (Hf-Zr-Nb)C powder is first prepared by carbon thermal reduction method. Then, the solid solution powder is pressed into tablets and placed in a pressureless sintering furnace to obtain a uniform and dense medium-entropy carbide ceramic block. (Hf-Zr-Nb)C ternary carbide medium-entropy ceramic has excellent high-temperature stability and ablation resistance, can withstand ablation of 2200°C oxyacetylene flame for 60 seconds, and has an intact structure. The present invention provides technical support for the use of multi-component carbide ceramics in aerospace hot end components.

[0009] A method for preparing high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramics, specifically comprising the following steps:

[0010] 1) Preparation of (Hf-Zr-Nb)C solid solution powder: weighing HfO2 powder, ZrO2 powder, Nb2O5 powder and C powder, ball milling and mixing, placing in a high-temperature heat treatment furnace with an inert atmosphere for high-temperature heat treatment, and obtaining (Hf-Zr-Nb)C solid solution powder by carbothermal reduction reaction;

[0011] 2) forming a carbide ceramic block: the obtained (Hf-Zr-Nb)C solid solution powder is fully mixed with a polyvinyl alcohol solution, poured into a mold, and pressed by a dry press to obtain a carbide ceramic block;

[0012] 3) Sintering the carbide ceramic block: placing the obtained carbide ceramic block in a high-temperature heat treatment furnace for sintering to obtain a dense carbide ceramic block.

[0013] As a preferred solution, the purity of the HfO2 powder, ZrO2 powder, Nb2O5 powder and C powder are all greater than 99.9%, and the particle sizes are all 1-3 μm.

[0014] As a preferred embodiment, the molar ratio of HfO2 powder, ZrO2 powder, Nb2O5 powder and C powder in step 1) is 1-3:1-3:0.5-2:10-30.

[0015] As a preferred solution, the ball milling in step 1) is carried out in a polytetrafluoroethylene ball mill, the grinding balls are made of ZrO2, the ball-to-material ratio is 3:1, and the ball milling is carried out at a speed of 200-400 r / min for 6-12 hours.

[0016] As a preferred solution, the heating rate of the high temperature heat treatment in step 1) is 3-7°C / min to 1900-2200°C.

[0017] As a preferred embodiment, the holding time of the high temperature heat treatment in step 1) is 1.5-2.5h.

[0018] As a preferred solution, the high temperature heat treatment in step 1) is followed by furnace cooling.

[0019] As a preferred embodiment, the concentration of the polyvinyl alcohol solution in step 2) is 0.008-0.028 g / L.

[0020] As a preferred solution, in step 2), the load pressure of the dry press is 20-40 MPa, the loading rate is 20-35 MPa / min, and the holding time is 1-5 min.

[0021] As a preferred solution, the sintering heating rate in step 3) is 3-7°C / min to 1900-2200°C and kept at this temperature for 1.5-2.5h, and then cooled in the furnace after sintering.

[0022] The advantages of the present invention compared with the prior art are:

[0023] 1. The present invention combines carbon thermal reduction and pressureless sintering to prepare (Hf-Zr-Nb)C ternary carbide medium-entropy ceramics. The oxyacetylene ablation test proves that it has better ablation resistance and solves the problems of loose structure, cracking and peeling of binary carbide ceramics after ablation.

[0024] 2. The (Hf-Zr-Nb)C ternary carbide medium-entropy ceramics prepared by the present invention have a dense surface after oxyacetylene ablation, a low ablation temperature, and good synergy between elements, showing excellent anti-ablation performance, laying a theoretical foundation for subsequent research on the anti-ablation performance of carbide medium / high entropy ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the XRD spectrum of the (Hf-Zr-Nb)C ceramic block of Example 1 before ablation.

[0026] Figure 2 This is the XRD spectrum of the (Hf-Zr)C ceramic block of comparative example 1 before ablation.

[0027] Figure 3 This is the XRD spectrum of the (Hf-Zr-Nb)C ceramic block in Example 1 after ablation for 60 seconds.

[0028] Figure 4 This is the XRD spectrum of the (Hf-Zr)C ceramic block in Example 1 after ablation for 60 seconds.

[0029] Figure 5 This is the microscopic morphology and EDS analysis diagram of the (Hf-Zr-Nb)C ceramic in Example 1 after 60s of ablation.

[0030] Figure 6 This is the microscopic morphology and EDS analysis diagram of the (Hf-Zr)C ceramic in Example 1 after ablation for 60 seconds.

[0031] Figure 7 Example 1 (Hf-Zr-Nb) C at 2.4MW / m 2 : Morphology before and after ablation under 30s ablation conditions.

[0032] Figure 8 Example 1 (Hf-Zr-Nb) C at 2.4MW / m 2 : Morphology before and after ablation under 60s ablation conditions.

[0033] Fig. 9 Comparative Example 1 (Hf-Zr) C at 2.4MW / m 2 : Morphology before and after ablation under 30s ablation conditions.

[0034] Fig.10 Comparative Example 1 (Hf-Zr) C at 2.4MW / m 2 : Morphology before and after ablation under 60s ablation conditions. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes. DETAILED DESCRIPTION

[0037] Example 1

[0038] Step 1: Weigh HfO2 powder, ZrO2 powder, Nb2O5 powder and C powder in a molar ratio of 2:2:1:19, pour the weighed powder into a polytetrafluoroethylene ball mill with a ball-to-material ratio of 3:1, add industrial alcohol and wet grind for 8 hours, and place in a constant temperature drying oven at 70°C for 10 hours. After this step, a uniform oxide mixed powder can be obtained. The oxide mixed powder is poured into a graphite crucible with an inner wall coated with graphite paper, and then placed in a high-temperature heat treatment furnace protected by Ar gas, with a heating rate of 5°C / min. After heating to 2100°C, it is kept warm for 2 hours and then naturally cooled with the furnace; the (Hf-Zr-Nb)C solid solution block is prepared by carbon thermal reduction reaction, placed in a polytetrafluoroethylene ball mill with a ball-to-material ratio of 3:1, and wet-milled with industrial alcohol for 8 hours, and then placed in a constant temperature drying oven at 70°C for 10 hours. After this step, the (Hf-Zr-Nb)C medium-entropy ceramic powder can be obtained.

[0039] Step 2: Take 5 g of the (Hf-Zr-Nb)C medium entropy ceramic powder obtained in step 1 and place it in an agate mortar. Use a rubber dropper to add 3 drops of PVA solution. Grind for 10 minutes and pour in Cr 12 In the MoV mold, the mold is placed under the dry press head, the load pressure is set to 30MPa, and the pressure is maintained for 1.5 minutes before unloading. After this step, a preliminarily formed (Hf-Zr-Nb)C medium-entropy ceramic embryo can be obtained.

[0040] Step 3: Wrap the (Hf-Zr-Nb)C medium-entropy ceramic body obtained in step 2 with graphite paper, place it in a graphite crucible with an inner wall coated with graphite paper, and then place it in a high-temperature heat treatment furnace protected by Ar gas. The heating rate is 5°C / min. After heating to 2100°C, keep warm for 2h, and then cool naturally in the furnace. After this step, a densely sintered (Hf-Zr-Nb)C medium-entropy ceramic block is obtained.

[0041] Figure 1 is the XRD spectrum of (Hf-Zr-Nb)C ceramic block before ablation. Figure 1 It can be seen that (Hf-Zr-Nb)C medium-entropy ceramics are obtained by carbothermal reduction reaction.

[0042] The prepared (Hf-Zr-Nb)C medium entropy ceramic block was subjected to oxyacetylene ablation test. The heat flux density of the oxyacetylene flame was 2.4MW / m 2 , where the acetylene gas flow is 0.18L / s, the oxygen gas flow is 0.24L / s, the acetylene pressure is 0.095MPa, the oxygen pressure is 0.4MPa, and the ablation time is 30s and 60s respectively. After 30s of ablation, only a few cracks appeared on the surface of the ceramic block, and the size was small. After 60s of ablation, there was still no obvious peeling on the surface of the ceramic block. Figure 3This is the XRD spectrum of the (Hf-Zr-Nb)C ceramic block after 60s of ablation. It can be seen from the figure that the oxide layer after ablation is mainly composed of high melting point oxide (Hf, Zr)O2 and low melting point oxide Zr6Nb2O 17 composition. Figure 5 The surface morphology and EDS analysis of (Hf-Zr-Nb)C ceramic after 60s ablation. It can be seen that the low melting point oxide Zr6Nb2O 17 It can well fill the gaps and cracks around the high melting point oxide, play a good bonding role, and inhibit the large-scale peeling of the oxide layer. 17 In the process of melting and volatilization, more heat is taken away, the ablation temperature of the ceramic is reduced, and the thermal stress concentration is reduced. In addition, the dense oxide layer can prevent oxygen-containing gas from further penetrating into the interior of the ceramic, playing a role in resisting further erosion by oxidizing gas.

[0043] Comparative Example 1

[0044] Step 1: Weigh HfO2 powder, ZrO2 powder and C powder in a molar ratio of 1:1:6, pour the weighed powder into a polytetrafluoroethylene ball mill with a ball-to-material ratio of 3:1, add industrial alcohol for wet grinding for 8 hours, and place it in a constant temperature drying oven at 70°C for drying for 10 hours. After this step, a uniform oxide mixed powder can be obtained. Pour the oxide mixed powder into a graphite crucible with a graphite paper coated inner wall, and then put it into a high-temperature heat treatment furnace with Ar gas protection, with a heating rate of 5°C / min, and heat it to 2100°C for 2 hours, and then cool it naturally with the furnace. The (Hf-Zr)C solid solution block is obtained by carbon thermal reduction reaction, and is placed in a polytetrafluoroethylene ball mill with a ball-to-material ratio of 3:1, and industrial alcohol is added for wet grinding for 8 hours, and placed in a constant temperature drying oven at 70°C for drying for 10 hours. After this step, (Hf-Zr)C medium entropy ceramic powder can be obtained.

[0045] Step 2: Take 5 g of the (Hf-Zr)C medium entropy ceramic powder obtained in step 1 and place it in an agate mortar. Use a rubber-tipped dropper to add 3 drops of PVA solution. Grind for 10 minutes and pour in Cr 12 In the MoV mold, the mold is placed under the dry press head, the load pressure is set to 30MPa, and the pressure is maintained for 1.5 minutes before unloading. After this step, a preliminarily formed (Hf-Zr)C medium-entropy ceramic embryo can be obtained.

[0046] Step 3: Wrap the (Hf-Zr)C medium-entropy ceramic body obtained in step 2 with graphite paper, place it in a graphite crucible with an inner wall coated with graphite paper, and then place it in a high-temperature heat treatment furnace protected by Ar gas. The heating rate is 5°C / min. After heating to 2100°C, keep warm for 2h, and then cool naturally in the furnace. After this step, a densely sintered (Hf-Zr)C medium-entropy ceramic block is obtained.

[0047] Figure 2 is the XRD spectrum of (Hf-Zr)C ceramic block before ablation. Figure 2 It can be seen that (Hf-Zr-Nb)C medium-entropy ceramics are obtained by carbothermal reduction reaction.

[0048] The prepared (Hf-Zr)C medium entropy ceramic block was subjected to oxyacetylene ablation test. The oxyacetylene heat flux density was 2.4MW / m 2 , where the acetylene gas flow is 0.18L / s, the oxygen gas flow is 0.24L / s, the acetylene pressure is 0.095MPa, the oxygen pressure is 0.4MPa, and the ablation time is 30s and 60s respectively. The (Hf-Zr)C ceramic block prepared by combining the carbon thermal reduction method and the pressureless sintering method has several through-cracks on the macroscopic surface of the ceramic block after ablation for 30s. These cracks penetrate each other to form larger cracks, and the oxide layer partially peels off. After ablation for 60s, the oxide layer on the surface of the ceramic block has completely peeled off, and only a small amount of ceramic oxide remains on the surface of the ceramic block. Figure 4 This is the XRD spectrum of the (Hf-Zr)C ceramic block after 60s of ablation. It can be seen from the figure that the oxide layer after ablation is mainly a high-melting-point (Hf, Zr)O2 solid solution. Figure 6 This is the microscopic morphology and EDS analysis diagram of (Hf-Zr)C ceramic after 60s of ablation. It can be seen that the oxide of (Hf-Zr)C ceramic after ablation is rich in Hf and Zr elements, has a high melting point, and is loose and porous. During the ablation process, the mechanical scouring causes the oxide layer to crack and peel off.

[0049] Table 1

[0050]

[0051] Comparison of anti-ablation performance between Example 1 and Comparative Example 1

[0052] Existing sintering processes usually use spark plasma sintering or hot pressing sintering equipment, which is very expensive and consumes a lot of energy. It is not suitable for mass production and is only suitable for processing small-sized and simple-shaped components. This solution uses pressureless sintering, which can put ceramic embryos of different shapes into a heat treatment furnace for batch sintering, with high yield, simple operation and low cost.

[0053] Traditional HfC and ZrC ceramics have high melting points (3890℃ and 3890℃), and their oxide melting points are also high (2810℃ and 2677℃), which means that they can play a good skeleton role when facing high-temperature flame flow. However, in contrast, under high thermal stress, once it cracks, oxygen will diffuse rapidly inward. If there is no molten phase to fill the cracks and pores, the oxygen erosion on the ceramic surface will be further deepened. The formed ceramic oxide cannot withstand the erosion of the high-speed oxyacetylene flame flow, so it peels off, causing a chain reaction, and continues to promote the diffusion of oxygen-containing gas flow, thus achieving a vicious cycle. Compared with HfC and ZrC ceramics, the melting point of NbC ceramics is 3000℃, and the melting point of its oxide is only 1520℃, which is lower than the melting point of the oxides of high-melting-point ceramics such as HfC, ZrC, TaC, and TiC, and is lower than the actual test temperature of oxyacetylene. Therefore, this paper adopts carbothermal reduction method to prepare a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic. The ablation test is carried out on it by oxyacetylene ablation equipment for 30s and 60s respectively. The phase analysis of the ablated oxide layer is carried out by XRD data. The results show that the Nb-rich low melting point oxide Zr6Nb2O 17 (melting point is 2040℃), and high melting point oxide (Hf,Zr)O2 (melting point is 2715℃). During the ablation process, the high melting point oxide acts as a skeleton phase, and the low melting point oxide fills holes and cracks. The above components work together to make the oxide layer dense and stable during the ablation process, preventing further penetration of oxygen, which significantly improves the ablation resistance of the ceramic with this component.

[0054] The present invention and its embodiments are described above, which is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it and do not deviate from the purpose of the invention, they can creatively design a structure and embodiment similar to the technical solution, which should fall within the protection scope of the present invention.

Claims

1. A method for preparing high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramics, characterized in that: The specific steps include: 1) Preparation of (Hf-Zr-Nb)C solid solution powder: weighing HfO2 powder, ZrO2 powder, Nb2O5 powder and C powder, ball milling and mixing, placing in a high-temperature heat treatment furnace with an inert atmosphere for high-temperature heat treatment, and obtaining (Hf-Zr-Nb)C solid solution powder by carbothermal reduction reaction; 2) forming a carbide ceramic block: the obtained (Hf-Zr-Nb)C solid solution powder is fully mixed with a polyvinyl alcohol solution, poured into a mold, and pressed by a dry press to obtain a carbide ceramic block; 3) Sintering the carbide ceramic block: placing the obtained carbide ceramic block in a high-temperature heat treatment furnace for sintering to obtain a dense carbide ceramic block.

2. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: The purity of the HfO2 powder, ZrO2 powder, Nb2O5 powder and C powder are all greater than 99.9%, and the particle sizes are all 1-3 μm.

3. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: The molar ratio of HfO2 powder, ZrO2 powder, Nb2O5 powder and C powder in step 1) is 1-3:1-3:0.5-2:10-30.

4. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: The ball milling described in step 1) is carried out in a polytetrafluoroethylene ball mill, the grinding ball material is ZrO2, the ball-to-material ratio is 3:1, and the ball milling mixing is carried out at a speed of 200-400r / min for 6-12h.

5. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: The heating rate of the high temperature heat treatment in step 1) is 3-7°C / min to 1900-2200°C.

6. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: The holding time of the high temperature heat treatment described in step 1) is 1.5-2.5h.

7. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: Step 1) After the medium-high temperature heat treatment, the product is cooled in the furnace.

8. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: The concentration of the polyvinyl alcohol solution in step 2) is 0.008-0.028 g / L.

9. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: In step 2), the load pressure of the dry press is 20-40 MPa, the loading rate is 20-35 MPa / min, and the holding time is 1-5 min.

10. The method for preparing a high temperature ablation resistant (Hf-Zr-Nb)C ternary carbide medium entropy ceramic according to claim 1, characterized in that: The sintering heating rate in step 3) is 3-7°C / min to 1900-2200°C and kept at this temperature for 1.5-2.5h, and then cooled in the furnace after sintering.

Citation Information

Patent Citations

  • ZrHfTaNbTiC ultrahigh-temperature high-entropy ceramic material as well as preparation method thereof

    CN108911751A

  • Method for preparing compact (HfZrTaNbTi) C high-entropy ceramic sintered body through normal-pressure sintering

    CN111410536A

  • High-entropy carbide ultrahigh-temperature ceramic powder and preparation method thereof

    CN113880580A

  • Carbon / carbon composite material surface (HfZrTi) C3 medium-entropy carbide ablation-resistant coating and preparation method thereof

    CN114853506A

  • Dual Phase High Entropy Boride-Carbide Composites for Extreme Environments

    US20240287657A1